Alat Deteksi Kandungan Gas CO Dan NO2 Via SMS - Yudhi Yudhi; Aan Febriansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2016)
Increasing the amount of air pollution that causes global warming and the lack of attention to harmful gases such as CO and NO2 can have negative effects on health can even cause death if it is ignored by those who breathe it. And one of the most popular communications media today is mobile. Therefore, it is necessary to create a tool that can monitor air quality levels and by utilizing advances in technology monitoring system can be seen from a far via SMS. In this paper, we use the type ATmega AVR microcontroller unit 16 as a control center and a GSM modem as a network system that handles communication between the microcontroller to the network using the SMS application. In addition, the system uses the C language as the configuration between the microcontroller and mobile network systems. Air pollution levels were measured with gas sensor MQ-7 that serves to measure levels of CO and MQ-5 to measure NO2 levels. The test results of sensor calibration and sensor MQ-5 MQ-7 which issued the ADC output is changed by using the formula provisions ppm ADC becomes a value in accordance with the standards set by ISPU (Air Pollution Standards Index).